Enhancement of Bacterial Infections in Mice by Newcastle Disease Virus - Hugh, Rudolph (1971)
This report describes an attempt to define the factors which incite secondary bacterial pneumonias. Groups of mice were given bacteria intraperitoneally and, at various intervals, Newcastle disease virus intravenously. There was an increase in the number of deaths and in the rates of death in these groups, when compared with a control group which was given only bacteria. These results were obtained with Streptococcus pneumoniae (Diplococcus pneumoniae), Pseudomonas aeruginosa, and Salmonella enteritidis ser. typhimurium. Newcastle disease virus increased the mortality rate of mice with bacterial infections when the two agents were given within 24 hr.